Clube de Ciências: desenvolvendo competências brincando - OLIVEIRA, Adriano José de (2009)
This work uses recreational activities in the teaching of science to the development of skills in high school students in a public school network. A theoretical discussion is made with respect to recreational activities, science club, and skills and competencies. As well as describes the method used and its characterization. We have made nine Science Club activities, which were made using texts and discussions, card game, another text to discussion, class exhibition of two teachers using experimentation, use of magazines - Veja, Isto é, Época, Tititi e Química Nova na Escola - for the learning of science, delivery of a text for discussion, two activities to form a chemical jury and finally the theatrical game - Chlorine Chemistry Jury. These applications within the science club proved to be an alternative for the development of the field of competence, due to almost 100% of our participants have acquired the skills and competencies desired. Finally, it is concluded that the teacher should always innovate and try to qualify.